2014
DOI: 10.1039/c3ay41636d
|View full text |Cite
|
Sign up to set email alerts
|

Biases in ketone measurements using DNPH-coated solid sorbent cartridges

Abstract: This paper examines the collection efficiencies of acetone and methyl ethyl ketone under different relative humidities, flow rates, and sample durations, for ambient sampling and laboratory experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…However, omitting datapoints with dew point > 7 • C markedly improved the agreement between the DNPH and PTR-MS measurements of acetone, with the results of the RMA analysis changing to a slope of 1.40 ± 0.14, an intercept of 0.22 ± 0.12 and an R 2 of 0.89 (N = 12) when wateraffected samples were omitted. Ho et al (2014) also identified a significant negative bias in the collection efficiency of acetone on DNPH cartridges that was related to humidity, sample flow rate and sample duration. While Ho et al (2014) used a similar DNPH cartridge type, these authors reported 35-80 % of acetone was lost under similar conditions as those experienced in this study (RH > 70 %, sample flow 1 L min −1 , sample duration 8-10 h).…”
Section: Acetonementioning
confidence: 99%
See 1 more Smart Citation
“…However, omitting datapoints with dew point > 7 • C markedly improved the agreement between the DNPH and PTR-MS measurements of acetone, with the results of the RMA analysis changing to a slope of 1.40 ± 0.14, an intercept of 0.22 ± 0.12 and an R 2 of 0.89 (N = 12) when wateraffected samples were omitted. Ho et al (2014) also identified a significant negative bias in the collection efficiency of acetone on DNPH cartridges that was related to humidity, sample flow rate and sample duration. While Ho et al (2014) used a similar DNPH cartridge type, these authors reported 35-80 % of acetone was lost under similar conditions as those experienced in this study (RH > 70 %, sample flow 1 L min −1 , sample duration 8-10 h).…”
Section: Acetonementioning
confidence: 99%
“…Ho et al (2014) also identified a significant negative bias in the collection efficiency of acetone on DNPH cartridges that was related to humidity, sample flow rate and sample duration. While Ho et al (2014) used a similar DNPH cartridge type, these authors reported 35-80 % of acetone was lost under similar conditions as those experienced in this study (RH > 70 %, sample flow 1 L min −1 , sample duration 8-10 h). These authors proposed a plausible explanation for the observed behaviour: when carbonyls pass through the DNPH sorbent, reactions occur involving the addition of the -NH 2 group to the -C=O group to form a reaction intermediate.…”
Section: Acetonementioning
confidence: 99%
“…Fu et al (2008) calculated production rates of 110 and 10 Tg year −1 from the oxidation of isoprene and acetone, re-spectively. Other precursors of MGLY are C 3 -C 5 isoalkanes (Jacob et al, 2002), aromatic compounds (Volkamer et al, 2001;Wu et al, 2014), and monoterpenes (Fick et al, 2003;Nunes et al, 2005). Due to the anthropogenic and biogenic natures of MGLY precursors, this compound can therefore be found at significant levels (low tens to hundreds of pptv) in urban, rural or even remote and marine environments (Henry et al, 2012 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al (2014) identified a significant negative bias in the collection efficiency of acetone on DNPH cartridges that was related to humidity, sample flow rate and sample duration. While Ho et al (2014) used a similar DNPH cartridge type, these authors Atmos. Meas.…”
Section: Acetonementioning
confidence: 99%